Oil spill environmental forensics : fingerprinting and source identification - Wang, Zhendi; Stout, Scott A. (Elsevier/Academic Press, 2007)
Oil Spill Environmental Forensics provides a complete view of the various forensic techniques used to identify the source of an oil spill into the environment. The forensic procedures described within represent various methods from scientists throughout the world. The authors explore which analytical and interpretative techniques are best suited for a particular oil spill project. This handy reference also explores the use of these techniques in actual environmental oil spills. Famous incidents discussed include the Exxon Valdez incident in 1989 and the Guanabara Bay, Brazil 2000. The authors chronicle both the successes and failures of the techniques used for each of these events. Dr. Zhendi Wang is a senior research scientist and Head of Oil Spill Research of Environment Canada, working in the oil and toxic chemical spill research field. He has authored over 270 academic publications and won a number of national and international scientific honors and awards. Dr. Wang is a member of American Chemical Society (ACS), the Canadian Society for Chemistry (CSC), and the International Society of Environmental Forensics (ISEF). *International experts show readers the forensic techniques used in oil spill investigations *Provides the theoretical basis and practical applications for investigative techniques *Contains numerous case studies demonstrating proven techniques.